Navigating “Revolution” in Henri Lefebvre’s Literary Corpus: An Academic Inquiry with Relevance to Contemporary Political Dynamics - Francesco Biagi (Práticas da História)
This article aims to rediscover and analyze overlooked works by Henri Lefebvre (1901–1991) that demonstrate his engagement with historical analysis, challenging stereotypes that confine him to urban or cultural studies. His work addresses the intertwined issues of “revolution” and “history” within 20th-century Marxist debate. The first section explores Lefebvre’s concept of “revolution” within critical urban theory and the theory of everyday life. The second section delves into his anti-determinist, anti-historicist approach to history within Marxist discourse. The third section examines his “progressive-regressive” method, tracing its roots in Marx and Engels’ thought, and its value for historical analysis and contemporary uses of the past. Ultimately, this article highlights Lefebvre’s significant contribution to rethinking the concept of “revolution” and its enduring implications.